Thermal Modeling of Indirect Solar Drying System: An Experimental Validation - Shukla, S.K.; Srivastava, A.K (Distributed Generation & Alternative Energy Journal, 2017)
The expressions for crop and moist air temperatures, drying rate and efficiency of indirect solar drying with phase change material (PCM) storage systems in quasi-steady state conditions have been derived. The analysis is based on the basic energy balance for the system. A computer model has been developed to predict the performance of the solar dry- ers. Experimental validation of the thermal model has been carried out by using modified heat transfer coefficients. Internal heat and mass transfer coefficients have been evaluated with PCM for March 24, 2014 in Varanasi, India. A fair agreement has been observed between theoretical and experimental results by using the modified internal heat and mass transfer coefficients.